1997
DOI: 10.1164/ajrccm.156.1.9606123
|View full text |Cite
|
Sign up to set email alerts
|

Revisited Physicochemical and Transport Properties of Respiratory Mucus in Genotyped Cystic Fibrosis Patients

Abstract: We investigated the physicochemical and transport properties of sputum samples collected in physiotherapy from a well-documented group of 27 cystic fibrosis (CF) patients with identified CF genotypes. Sputum samples were characterized ex vivo for their water content, surface properties (surface tension and contact angle), rheologic properties (viscosity and elastic modulus), and transport properties (mucociliary and cough transport). These data were analyzed in relation to the clinical status of the patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1
5

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 27 publications
3
26
1
5
Order By: Relevance
“…However, we estimated the percent dry weight (percentage of solids) of normal mucus at ϳ1.5-2.5% and of thick CF-like mucus at ϳ6 -15%, based on data reported from cell culture (26), a mouse model (4), and human studies (27)(28)(29)(30)(31)(32)(33). Mucus of 1.5% solids may be less than the normal optimal concentration because the network of mucin fibers and transport were heterogeneous (Fig.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…However, we estimated the percent dry weight (percentage of solids) of normal mucus at ϳ1.5-2.5% and of thick CF-like mucus at ϳ6 -15%, based on data reported from cell culture (26), a mouse model (4), and human studies (27)(28)(29)(30)(31)(32)(33). Mucus of 1.5% solids may be less than the normal optimal concentration because the network of mucin fibers and transport were heterogeneous (Fig.…”
Section: Figurementioning
confidence: 99%
“…1C), may reflect the concentration of mucins that occurs in larger airways due to increased mucin secretion and ASL volume absorption (36). The higher concentration of mucus we operationally chose to mimic CF, 6.5%, likely represents the minimum concentration found in CF airways before infection (29,30,32,33). Mucus transport assays demonstrated that 6.5% mucus was too thick to be transported by cilia, mimicking a key feature of CF mucus (2).…”
Section: Figurementioning
confidence: 99%
“…Although measurements of mucus concentration, i.e., the percentage of solids content, from CF subjects before infection have not been reported, estimates from cell cultures (11) and sputum (12)(13)(14)(15)(16)(17)(18) suggest that CF mucus is at least three or four times more concentrated than normal. Therefore, mucus was obtained from well differentiated human airway cultures and was isotonically concentrated (1) to produce mucus of normal (2.5% solids wt/wt) and CF-like (8%) concentrations (Fig.…”
mentioning
confidence: 99%
“…15 In our study the evaluation of macroscopic appearance of the secretions was always performed by 2 investigators. To reduce the subjectivity of those evaluations we used the scale described by Deneuville et al 9 Regarding the samples from the without-lung-disease subjects, the mucus analysis was difficult, because small amounts were collected, so for this group we applied the method described by Rubin et al, 8 in which mucus is collected from the endotracheal tube used during a short surgical procedure in without-lung-disease subjects. The characteristics of the mucus deposited inside and outside the tube was compared.…”
Section: Discussionmentioning
confidence: 99%
“…The mucus was assessed for purulence with a score based on a previously described numerical visual scale, 9 which ranges from 1 (mucoid) to 5 (yellow/green). Samples with a purulence index between 1 and 3 were classified as mucoid, and samples with scores of 4 or 5 were classified as purulent.…”
Section: Purulencementioning
confidence: 99%